2013
DOI: 10.1186/1868-7083-5-1
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of genetic variants and DNA methylation of the interleukin-4 receptor gene increase the risk of asthma at age 18 years

Abstract: BackgroundThe occurrence of asthma is weakly explained by known genetic variants. Epigenetic marks, DNA methylation (DNA-M) in particular, are considered to add to the explanation of asthma. However, no etiological model has yet been developed that integrates genetic variants and DNA-M. To explore a new model, we focused on one asthma candidate gene, the IL-4 receptor (IL4R). We hypothesized that genetic variants of IL4R in interaction with DNA-M at cytosine-phosphate-guanine (CpG) sites jointly alter the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 27 publications
1
91
1
Order By: Relevance
“…Yousefi et al (2013) found that the LEPR genotype interacted with maternal smoking to associate with methylation of LEPR. A SNP within the IL4R gene combined with methylation at a CpG site within the same gene predicts the risk of childhood asthma (Soto-Ramirez et al 2013). Moreover, Klengel et al (2013) found that interaction of the FKBP5 genotype and early childhood trauma affects methylation of FKBP5 intron 7, FKBP5 expression, and subsequent deregulation of glucocorticoid receptor signaling.…”
mentioning
confidence: 99%
“…Yousefi et al (2013) found that the LEPR genotype interacted with maternal smoking to associate with methylation of LEPR. A SNP within the IL4R gene combined with methylation at a CpG site within the same gene predicts the risk of childhood asthma (Soto-Ramirez et al 2013). Moreover, Klengel et al (2013) found that interaction of the FKBP5 genotype and early childhood trauma affects methylation of FKBP5 intron 7, FKBP5 expression, and subsequent deregulation of glucocorticoid receptor signaling.…”
mentioning
confidence: 99%
“…Though several previous studies have investigated statistical interactions between genetic and epigenetic variation [13][14][15]38], we know of no others that have attempted a genome-wide assessment. CASI identified 12 genomic regions defined by the positions of 12 genes with evidence of statistical interactions between sets of SNPs and sets of methylated CpGs with respect to asthma risk.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, interactions between SNPs and DNA methylation in the genomic regions of T-helper 2 pathway genes IL4R and others were found to affect asthma risk [14,15], possibly through expression of these genes.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic regulation of gene expression in airway epithelium is evident in inflammatory conditions like asthma, smoking, and infection; TSA has been instrumental in uncovering the role of histone acetylation in some of these studies (18,(31)(32)(33). Although TSA is an inhibitor of most of the class I and II HDAC proteins, its activity is restricted outside of the HDAC family of proteins (34).…”
Section: Discussionmentioning
confidence: 99%